1997
DOI: 10.1007/s001220050634
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of outcrossing rate in a breeding population of Eucalyptus urophylla with dominant RAPD and AFLP markers

Abstract: Eucalyptus breeding is typically conducted by selection in open-pollinated progenies. As mating is controlled only on the female side of the cross, knowledge of outcrossing versus selfing rates is essential for maintaining adequate levels of genetic variability for continuous gains. Outcrossing rate in an open-pollinated breeding population of Eucalyptus urophylla was estimated by two PCR-based dominant marker technologies, RAPD and AFLP, using 11 open-pollinated progeny arrays of 24 individuals. Estimated out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
11

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 17 publications
5
66
1
11
Order By: Relevance
“…This model has been successfully applied by different authors (Gaiotto et al, 1997;Muluvi et al, 2004;Muchugi et al, 2008) to species without available co-dominant markers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has been successfully applied by different authors (Gaiotto et al, 1997;Muluvi et al, 2004;Muchugi et al, 2008) to species without available co-dominant markers.…”
Section: Resultsmentioning
confidence: 99%
“…Dominant DNA markers, such as RAPD and AFLP, have been used to estimate outcrossing rates in Moringa oleifera (Muluvi et al, 2004) and Eucalyptus urophylla (Gaiotto et al, 1997), despite limitations on the correct genotypic identification of individuals. To overcome this limitation, Ritland (2002) developed the multilocus model to estimate outcrossing rates in plant species, so that dominant markers could be applied in mating system studies.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of fixed effects was tested using F-tests. The outcrossing rate in natural stands of E. urophylla has been estimated to be about 90% (House and Bell, 1994;Gaioto et al, 1997). This information was incorporated in the calculations of genetic parameters in ASReml by declaring a selfing rate of 10% in the population in the model (Gilmour et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…For Eucalyptus citriodora, Yeh et al (1983) reported an outcrossing rate of 85% estimated with isozymes. For Eucalyptus urophylla, Gaiotto et al (1997) estimated around 90% with RAPD and AFLP markers.…”
Section: Reproductive Behaviour Inside the Seed Orchardmentioning
confidence: 99%